LINGUISTIC DEVICES OF DEVELOPING TEXT FORMAL INTEGRITY - H. O. Matkovska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The article provides the profound insight into the principles and means of achieving the formal text integrity. The fundamental directions of the text study have been suggested. They include the purely linguistic approaches as well as the interdisciplinary ones. The notion of text has been specified within the structural-and-grammatical, semantic, communicative and semiotic approaches. The main standards of textuality have been discussed. The integrity as one of the crucial criteria pertaining to the text is associated with the standards of cohesion and coherence. The main divergences between the cohesion and coherence have been established. Cohesion is determined as a formal aspect of the textual integrity which is concerned with the lexicogrammatic relations within the text. The coherence as a content integrity is predetermined by the text theme. It has been stipulated that the communicative unity of the text is achieved through the information flow, establishing anaphoric or cataphoric relations throughout the informative structure of the text. The research has been aimed at the organization and characterizing of the principal linguistic devices used to provide the formal integrity. The cohesion is based on the formal iteration, which involves various types of recurrence, reference, ellipsis and substitution, and formal relation that is achieved by means of conjunction and word order.